A collection of Peracarida from Möre and Romsdal, Northwestern Norway - Brattegard, T. & Vader, W. (Sarsia, 1972)
This paper presents a list of species of Peracarida (3 Mysidacea, 24 Cumacea, 9 Tanaidacea, 20 Isopoda, and 62 Amphipoda), collected during a two week cruise (summer 1970) in the faunistically poorly investigated fjords and coastal areas of Möre and Romsdal county, northwestern Norway.
Ant'Phipoda Literature database NeMys doc_id: 384